The Reliability of the Density‐Functional Theory in Actinide Endohedral Systems. Issue 10 (2nd September 2019) - Wang, Jianpeng; Xie, Weiyu; Jiang, Wanrun; Wu, Xiaochen; Wang, Zhigang
Abstract: Density‐functional theory (DFT) has shown obvious violation to the Jacob's ladder in predicting the geometric and electronic structures of carbon‐based high‐Z elements endohedral metallofullerenes (hZ‐EMFs). This has aroused long‐term discussion in both theoretical and experimental fields, because this is related to whether the computationally efficient DFT can be the substitution to post‐HF. In this work, the violation to the Jacob's ladder emerges again on the boron based uranium endohedral structure U@B40 . The proper choice of functionals has been a significant factor to predict both geometric and electronic structures of U@B40 . Pure generalized gradient approximations (GGA) functionals give a high symmetrical singlet ground state of D2d, while a slightly tortured C2v triplet state is more stable when hybrid GGAs are used. Compared to pure GGAs triplet state, the spin density accumulates more obviously on its B40 cage in hybrid GGAs triplet state. The qualitative difference originates in the proportion of exact exchange energy that can exert a tremendous influence on energy splitting between electronic states of U@B40 . This controversial calculation is an ideal model to reestimate the role of exchange functionals in studying hZ‐EMFs. Therefore, these findings will provide important references to the benchmark experiments and future theoretical predictions. Abstract : This paper provides a theoretical study toward a boron‐based uranium endohedral metallofullerenes U@B40 . Its electronic and geometric structures can be grouped by functional types. Calculations show that the exact exchange term plays an important role in such a heavy element containing system.